Creative nonfiction: true stories of people involved in fifty years of conservation of the orang-utan in Sarawak, Malaysia - Yin, Christina Amanda Chueh Ping (2021)
This study explores the fourth genre, creative nonfiction, as the means to retell the stories of lived experiences. The aim of the study was to gather stories of ordinary people working to conserve orang-utans in Sarawak through in-depth interviews based on narrative inquiry principles, and then to re-tell the stories by crafting a creative nonfiction artefact composed of different subgenres such as Shorts, Portraits, Literary Journalism, hybrid nonfiction pieces and stories partially or wholly told in the participants’ own voices in a subgenre that the narrative inquirer-writer identified and named the Crafted Interview.